GEOCHEMICAL AND STATISTICAL ANALYSIS OF TRACE METALS IN ATMOSPHERIC PARTICULATES IN WUHAN, CENTRAL CHINA - Lv W.; Wang Ya.; Querol X.; Zhuang X.; Alastuey A.; López A.; Viana M. (My University, 2006)
The geochemical characteristics of trace metals (As, Cr, Co, Cd, Cu, Mn, Ni, Pb, V and Zn) in PM10 in Wuhan, the biggest metropolitan in central China, as well as their sources and contributions were analyzed. As PM10 has been the principal contaminant of air in Wuhan for years, concentrations of trace metals were measured in PM10 using high-volume samplers at one urban (Hankou) and one industrial (Changqian) site in Wuhan between September 2003 and September 2004. Based on the results, PM10 in Wuhan is characterized by relatively high levels of As, Cd, Mn, Pb and Zn compared with other Asian cities. The time-series of these elements indicated that As, Cu and Zn at both sites have similar trends, whereas Pb levels showed different patterns due to different emission sources. Factor analysis was applied to the datasets focusing on the apportionment of the mass of selected trace metals. Results indicate that Pb, Cd and As have a common source (smelting) at both sites, whereas the sources of Ni vary from coal combustion and steel in Changqian to mineral and traffic in Hankou.
Keywords: PM10; GEOCHEMISTRY; STATISTIC ANALYSIS; TIME SERIES